ANALYSIS OF FOREIGN EXPERIENCE OF DEVELOPMENT OF COMPETITION AT RETAIL ELECTRICITY MARKETS: UK AND NORTHERN EUROPE COUNTRIES EXPERIENCE - O. Mozgovaya (Вестник университета)
Promotion of competition at retail electricity markets and electric power industry liberalization are the worldwide trends. The rewarding experience of retail electricity markets performance demonstrates that the deregulated model of wholesale and retail electricity markets provides mostfavorite competitive mechanism. The UK and Northern Europe countries (Norway, Sweden, Finland, Denmark) competitive mechanisms practiced at retail electricity markets have analysed. The deregulated model of wholesale and retail electricity markets distinctive features has determined, also the applied types of electricity supply contract and tariffs, the special aspects of electric power pricing for ultimate customers have perceived.